Catalase-Negative Staphylococcus lugdunensis Strain with a Novel Point Mutation in the Catalase Gene Isolated from a Patient with Chronic Suppurative Otitis Media - Lu, Yong; Wang, Yiping; Ling, Buzhi; Ke, Xianfu; Ying, Jianfei; Yu, Yanhong; He, Mingyang; Li, Xiangyang (Journal of Clinical Microbiology, 2013)
Errata ( vol. 52 , p. 708 ) Article Usage Stats Services JCM Citing Articles Google Scholar PubMed Related Content Social Bookmarking CiteULike Delicious Digg Facebook Google+ Mendeley Reddit StumbleUpon Twitter current issue JCM About JCM Subscribers Authors Reviewers Advertisers Inquiries from the Press Permissions & Commercial Reprints ASM Journals Public Access Policy JCM RSS Feeds 1752 N Street N.W. • Washington DC 20036 202.737.3600 • 202.942.9355 fax • journals@asmusa.org Print ISSN: 0095-1137 Online ISSN: 1098-660X Copyright © 2014 by the American Society for Microbiology. For an alternate route to JCM .asm.org, visit: JCM